Isoelectric Focusing of Serum Apolipoprotein C-III as a Sensitive Screening Method for the Detection of O-glycosylation Disturbances - Ondrušková, Nina; Honzík, Tomáš; Kytnarová, Jitka; Matoulek, Martin; Zeman, Jiří; Hansíková, Hana (Prague medical report, 2015)
Apolipoprotein C-III (ApoC-III) is a glycoprotein carrying the most common O-linked glycan structure and is abundantly present in serum, what renders it a suitable marker for analysis of O-glycosylation abnormalities. Isoelectric focusing followed by a Western blot of ApoC-III, using PhastSystem™ Electrophoresis System (GE Healthcare), was introduced as a rather simple and rapid method for screening of certain subtypes of inherited glycosylation disorders. The study's aim was to establish this method in our laboratory, what included performing the analysis in a group of 170 healthy individuals to set the reference range of detected relative amounts of sialylated ApoC-III isoforms and to evaluate the gender- and age-dependent differences. A significant relative increase of asialo-ApoC-III with growing age was found. Secondly, we examined serum from patients with selected metabolic disorders and detected minor O-glycosylation changes in diseases such as Prader-Willi syndrome, PGM1 (phosphoglucomutase 1) or MAN1B (class 1B alpha-1,2-mannosidase) deficiency. Our results show that this method allows for a sensitive detection of ApoC-III O-glycosylation status, however this might be modulated by several factors (i.e. nutrition, medication) whose exact role remains to be determined.
Keywords: novorozenec; Infant, Newborn; Infant; Humans; kojenec; dítě; Child; Metabolism, Inborn Errors; Female; dospělí; Blotting, Western; apolipoprotein C-III; lidé; Apolipoprotein C-III; protein - isoformy; předškolní dítě; Adult; Protein Isoforms; ženské pohlaví; glykosylace; isoelektrická fokusace; Male; vrozené poruchy metabolismu; Adolescent; Isoelectric Focusing; Mass Screening; plošný screening; western blotting; mužské pohlaví; Child, Preschool; Glycosylation; mladiství